2021
DOI: 10.1002/ejoc.202100414
|View full text |Cite
|
Sign up to set email alerts
|

4‐(Di‐/Trifluoromethyl)‐2‐heterabicyclo[2.1.1]hexanes: Advanced Fluorinated Phenyl Isosteres and Proline analogues

Abstract: A gram-scale synthesis, physico-chemical characterization, and lead-likeness assessment of 4-di/trifluoromethyl-2-heterabicyclo [2.1.1]hexanes as fluorinated bicyclic proline analogues and phenyl isosteres are disclosed. The key step of the synthesis included iodocyclization of fluorinated 3-hydroxy-/3aminomethyl methylenecyclobutanes; with the amino derivatives, the reaction was accompanied with carboxylation and further cyclization. Apart from the corresponding 4-di/ trifluoromethyl-2,4-methanoprolines, a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…[33] In the latter one, iodocyclization of alkenols 93 was applied. [428,429] In both cases, physicochemical and biological characterization of the designed scaffolds was performed, which confirmed their geometric similarity with the corresponding benzene derivatives and higher aqueous solubility.…”
Section: Non-classical Sp 3 -Enriched Benzene Isosteres: An Escape From Flatlandmentioning
confidence: 60%
“…[33] In the latter one, iodocyclization of alkenols 93 was applied. [428,429] In both cases, physicochemical and biological characterization of the designed scaffolds was performed, which confirmed their geometric similarity with the corresponding benzene derivatives and higher aqueous solubility.…”
Section: Non-classical Sp 3 -Enriched Benzene Isosteres: An Escape From Flatlandmentioning
confidence: 60%
“…Despite successful exemplification of this isostere, the angle between substituents (ϕ), and hence exit vectors, are deviated from the parent compound. It should be noted that recent efforts have shown that oxa-21 and aza-variants 22 are useful in increasing water solubility of this scaffold. In addition, a recent study described the introduction of 1,2-disubstituted-[1.1.1]-bicyclopentanes to serve as metaand ortho-substituted aromatic ring replacements (Fig.…”
mentioning
confidence: 99%
“…Both compounds 1 and 2 are convenient intermediates for further transformations and were applied for the preparation of various promising building blocks. Continuing our research in this area [4][5][6][7][8][9], in this paper we further demonstrate the synthetic potential of compounds 1 and 2 and present synthesis of novel building blocks 3-6 that combine the 1,3-substituted cyclobutane motifs and the CF3 moiety near the functional group in their structure.…”
Section: Introductionmentioning
confidence: 57%
“…Recently, [2+2] cycloaddition reaction between allene and α-CF3-acrylonitrile was described [3]. Resulting methylene-containing nitrile 1 was used for the preparation of carboxylic acid 2 on a multigram scale [3,4]. Both compounds 1 and 2 are convenient intermediates for further transformations and were applied for the preparation of various promising building blocks.…”
Section: Introductionmentioning
confidence: 99%